COMPARATIVE ANALYSIS OF UV-C AND UV-B RADIATION INFLUENCE ON PLANT OBJECTS - Міхєєв, О.; Тихенко, О. (Proceedings of National Aviation University (archive), 2012)
General aim of work – comparative research of temporal regularities of growth processes of pea, that was grown under normal conditions and with application of UV-C and UV-B irradiation of stem part, and also detection of irradiation dose relations to parameter of root and stem part sprouts growth rate of Aronis pea. Research subject of UV-C and UV-B irradiation influence on dynamics of plant growth parameters in each set of experiments was alteration of growth rate, pecularities of growth dynamics in different conditions of experiment, detection of UV-C and UV-B irradiation doses range, that stimulate or inhibit growth parameters of pea sprouts. The investigation resulted in determination 1,3 times higher efficiency of UV-V irradiation comparing to UV-B irradiation. Reaction of root didn’t depend on the type of UV-radiation